Perlindungan Hukum terhadap Anak sebagai Pelaku Penyalahgunaan Narkotika melalui Media Digital: Studi Kompratif Hukum Islam dan Hukum Positif Indonesia - Yusril Aulia Patra; Muchamad Iksan; Wardah Yuspin (Indo Publishing, 2026)
Drug abuse by children is now developing through new patterns based on digital technology, such as transactions via social media, encrypted communication, and the influence of online social media. This situation places children in two positions simultaneously: as perpetrators of drug abuse and as victims of telematic crimes that exploit their vulnerability. This article analyzes the legal protection of children as perpetrators of drug abuse through digital media using a comparative approach between Islamic law and Indonesian positive law. Using a normative juridical method, this study finds that Islamic law emphasizes the protection of the soul and mind through the maqashid sharia, so that moral rehabilitation and spiritual development are priorities in child care. Meanwhile, Indonesian positive law, through the SPPA Law and the Narcotics Law, positions children as parties who must be protected with a rehabilitative and restorative justice approach, including when drug abuse is carried out through electronic means. The results of the study indicate that the development of telematic modes in drug abuse requires stronger harmonization between Islamic legal values and national regulations to provide comprehensive protection for children amid the rapid threat of digital crime against the younger generation.